CABG Surgery Remains the best Option for Patients with Left Main Coronary Disease in Comparison with PCI-DES: Meta-Analysis of Randomized Controlled Trials - Sá,Michel Pompeu Barros Oliveira (2017)
Abstract Objective: To compare the safety and efficacy of coronary artery bypass grafting (CABG) with percutaneous coronary intervention (PCI) using drug-eluting stents (DES) in patients with unprotected left main coronary artery (ULMCA) disease. Methods: MEDLINE, EMBASE, CENTRAL/CCTR, SciELO, LILACS, Google Scholar and reference lists of relevant articles were searched for clinical studies that reported outcomes at 1-year follow-up after PCI with DES and CABG for the treatment of ULMCA stenosis. Five studies fulfilled our eligibility criteria and they included a total of 4.595 patients (2.298 for CABG and 2.297 for PCI with DES). Results: At 1-year follow-up, there was no significant difference between CABG and DES groups concerning the risk for death (risk ratio [RR] 0.973, P=0.830), myocardial infarction (RR 0.694, P=0.148), stroke (RR 1.224, P=0.598), and major adverse cerebrovascular and cardiovascular events (RR 0.948, P=0.680). The risk for target vessel revascularization (TVR) was significantly lower in the CABG group compared to the DES group (RR 0.583, P<0.001). It was observed no publication bias regarding the outcomes, but only the outcome TVR was free from substantial statistical heterogeneity of the effects. In the meta-regression, there was evidence that the factor "female gender" modulated the effect regarding myocardial infarction rates, favoring the CABG strategy. Conclusion: CABG surgery remains the best option of treatment for patients with ULMCA disease, with lower TVR rates.